Ultradian Hemodynamics and Autonomic-Central Nervous System Activity During Sleep: A Pilot Study with Insights for Hypertension - David Shannahoff-Khalsa; Roy Schult; B. Bo Sramek (Mary Ann Liebert, 2022)
Introduction: Left stroke work index (LSWI) and stroke systemic vascular resistance index (SSVRI) were compared with an ultradian rhythm of the autonomic nervous system (ANS) called the nasal cycle (NC). LSWI measures myocardial contractility and SSVRI measures after load. Mean arterial pressure (MAP) versus stroke Index (SI) has been proposed to be a useful diagnostic for the pharmacological treatment of hypertension. The NC exhibits with an ultradian rhythm in the ?hourly like? range of alternating dominance of airflow through the two nostrils and is a marker of alternating lateralization of ANS activity throughout the periphery that is tightly coupled to the ultradian central nervous system (CNS) rhythm of alternating cerebral hemispheric dominance. Methods: Beat-to-beat measures of MAP versus SI were plotted over the sleep night in three healthy male subjects, each with three consecutive nights of sleep. The spectral time series analysis for LSWI, SSVRI, and the NC were compared, along with previously reported values for other ultradian measures in healthy adults during sleep and waking rest. Results: LSWI, SSVRI, and the NC have significant power in bins with periods at 280?300, 105?140, 70?100, and 40?65?min. The greatest spectral power is in longer periods. The NC also had a significant peak at 215?270?min. No significance for LSWI, SSVRI, or the NC was observed at 145?160 or 165?210?min. Discussion: These results suggest that LSWI and SSVRI are coupled to the NC and other ultradian rhythms regulated by the hypothalamus. MAP versus SI shows high variability and supports the importance of long-term sampling for the diagnosis and pharmacological treatment of hypertension. In addition, it is known that the yogic technique called unilateral forced nostril breathing can alter ANS, CNS, and the cardiovascular system. We expand here on the dynamics of hemodynamic states, and potentially how they may be altered to improve health.